Misconstruing Graham & Miller - Cara H. Drinan (Washington University Law Review, 2014)
In the last three years, the Supreme Court has decreed a sea change in its juvenile Eighth Amendment jurisprudence. In particular, in Graham v. Florida and Miller v. Alabama, the Court struck down a majority of the states’ juvenile sentencing laws by outlawing life without parole (“LWOP”) for juveniles who commit non-homicide offenses and by mandating individualized sentencing for juveniles who commit even the most serious murders. An examination of state laws and sentencing practices since these rulings, however, suggests that the Graham and Miller rulings have fallen on deaf ears. After briefly describing what these two decisions required of the states, in this Essay, I outline the many ways in which state actors have failed to comply with the Court’s mandate. Finally, I map out a path for future compliance that relies heavily upon the strength and agility of the executive branch.
Keywords: Eighth Amendment; Graham v. Florida; Miller v. Alabama; LWOP